2014
DOI: 10.1111/and.12268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychological stress on fertility hormones and seminal quality in male partners of infertile couples

Abstract: The present study evaluated the effect of psychological stress on male fertility hormones and seminal quality in male partner of infertile couples. Seventy male partners of infertile couples were evaluated for level of psychological stress using Hospital Anxiety and Depression Score (HADS) questionnaire, serum total testosterone, luteinising hormone (LH) and follicle-stimulating hormone (FSH) by electrochemiluminescence assay and serum GnRH by ELISA. Seminal analysis was performed as per WHO guideline. Ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 22 publications
(24 reference statements)
7
78
1
10
Order By: Relevance
“…Seventy infertile male partners were investigated as for psychological stress levels using Anxiety and Depression Scale scoring system and with measurements of total serum testosterone, serum GnRH, FSH, LH levels and spermiograms. The researchers indicated that psychological stress firstly lowers serum total testosterone levels, and secondarily increases serum LH and FSH levels, which suggest that stress management might have an important place in male infertility (17). We included only infertile male patients in our study and found depression rates in primary and secondary infertile groups as 22 and 38%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Seventy infertile male partners were investigated as for psychological stress levels using Anxiety and Depression Scale scoring system and with measurements of total serum testosterone, serum GnRH, FSH, LH levels and spermiograms. The researchers indicated that psychological stress firstly lowers serum total testosterone levels, and secondarily increases serum LH and FSH levels, which suggest that stress management might have an important place in male infertility (17). We included only infertile male patients in our study and found depression rates in primary and secondary infertile groups as 22 and 38%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Semua perasaan yang tidak menyenangkan itu jika berlaku secara kronik boleh mengganggu fungsi tubuh (Chrousos et al 2013). Stres yang berpanjangan boleh menyebabkan perubahan kepada keseimbangan hormon testosteron dalam badan (Levi 2013) yang mengganggu pembentukan sperma (Bhongade et al 2015).…”
Section: Pengenalanunclassified
“…Kajian terdahulu menyatakan stres meninggalkan implikasi negatif dalam pelbagai parameter yang berkait rapat dengan kualiti semen termasuk kepekatan sperma, motiliti dan morfologi (Bhongade et al 2015). Kajian kesan stres terhadap organ pembiakan manusia dan kualiti semen telah mendapat perhatian meluas sejak dahulu lagi (Barazani et al 2014).…”
Section: Pengenalanunclassified
See 1 more Smart Citation
“…Современные исследования показывают, что бесплодие приводит к стрессу, и в свою очередь стресс признан возможной причиной пато-спермии [1][2][3]. Диагноз «бесплодие» является провоцирующим фактором для депрессивного состояния.…”
unclassified